Endosymbiotic Bacteria Associated with the Mealy Bug, Rhizoecus amorphophalli (Hemiptera: Pseudococcidae) - Sreerag, Ravikumar Sreekala (Int Sch Res Notices, 2014)
The mealy bug, Rhizoecus amorphophalli, is a menace to the aroid farmers due to the intensive infestation on stored tubers. Spraying of pesticides was able to control this pest but it always left a chance for fungal growth. Bacterial endosymbionts associated with the insects provide several benefits to their host. Since such endosymbionts play a vital role even in the physiology of their host, revealing the types of bacteria associated with mealy bug will give basic information, which may throw light on the management of this noxious pest. The present study is the first to identify bacterial endosymbionts associated with R. amorphophalli employing phenotypic characterization and 16S rDNA sequencing. Three culturable bacteria, namely, Bacillus subtilis, Staphylococcus gallinarum, and Staphylococcus saprophyticus, were isolated from R. amorphophalli. Moreover, the antibiotic susceptibility tests against the isolated bacteria showed that all the isolates were susceptible to the three antibiotics tested, except cephalexin. Recently, endosymbionts are used as effective biocontrol agents (BCAs) and the present study will stand as a connecting link in identification and effective utilization of these endosymbionts as BCAs for management of R. amorphophalli.